A conceptual proposal of game theory-based strategy for contractor/owner conflict management in additional cost disputes - Jung, Sung Sik; Cha, Hee Sung (Journal of the Architectural Institute of Korea, 2025)
In the domestic construction industry, various uncertainties such as the COVID-19 pandemic and geopolitical conflicts have led to frequent interruptions at construction sites due to disputes over additional construction costs between contractors and owners. Unlike public construction projects, which are bound by strict contracts, private construction relies heavily on mutual agreements. Despite the critical need for effective conflict management among participants, the industry lacks appropriate regulations and measures to address such disputes. This study identifies the importance of decision-making in dispute situations between contractors and owners using the Analytic Hierarchy Process (AHP) technique and models these interactions through evolutionary game theory. By developing a simulation model, the study establishes a framework to mitigate conflicts among stakeholders. The proposed system is anticipated to contribute to effective conflict management through strategic decision-making in additional construction cost dispute scenarios.
Keywords: Additional cost; AHP; Evolutionary Game Theory; Simulation